The YouTube-assisted discovery learning model: Improving students’ cognitive learning outcomes and critical thinking - Wilma Akihary; Rita Fransina Maruanaya; Carolina Lestuny; Seplinovye Penina Maruanaya (Journal of Education and Learning (EduLearn), 2023)
The quality improvement of human resources in the society 5.0 era in the 21st century is closely related to technology, and one of the ways this can be achieved is by using YouTube. Therefore, this research determined the differences in student cognitive learning outcomes and critical thinking before and after applying the YouTube-assisted discovery model in German Language Education Study Program at Pattimura University, Indonesia. A pseudo-experiment a pretest and posttest unequal control group design was used to obtain 20 2nd semester students who took the course Strukturen und Wortschatz zur Aufbaustufe A2.1. Furthermore, the sample determination used a proportional sampling technique. Data collection was done using the instrument in the form of essays tests to determine the cognitive learning and critical thinking outcomes, questionnaire sheets, and interviews. The paired T-test showed a value of p=0.000α=0.05, indicating significant differences in cognitive learning outcomes and critical thinking skills before and after applying the YouTube-assisted discovery learning model. This was confirmed by an increase in the cognitive test scores and critical thinking of students after applying the learning model. Therefore, the results can be applied to other concepts in German language learning.